PEDAGOGICAL PROBLEMS OF PROFESSIONAL FORMATION COMPETENCIES OF FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2008)
In article pedagogic problems of formation of professional competence of the future teachers are considered.